Influence of cytokines, circulating markers and growth factors on liver regeneration and post-hepatectomy liver failure: a systematic review and meta-analysis - Murtha-Lemekhova, Anastasia; Fuchs, Juri; Ghamarnejad, Omid; Nikdad, Mohammedsadegh; Probst, Pascal; Hoffmann, Katrin (Scientific reports, 2021)
The pathophysiology of post-hepatectomy liver failure is not entirely understood but is rooted in the disruption of normal hepatocyte regeneration and homeostasis. Current investigations of post-hepatectomy liver failure and regeneration are focused on evaluation of circulating hepatic function parameters (transaminases, cholestasis, and coagulation parameters), volumetry and hepatic hemodynamics. However, identification of biochemical factors associated with regeneration and post hepatectomy liver failure is crucial for understanding the pathophysiology and identification of patients at risk. The objective of the present systematic review was to identify circulating factors associated with liver regeneration and post hepatectomy liver failure in patients undergoing hepatectomy. The quantitative analysis was intended if studies provided sufficient data. Electronic databases (MEDLINE via PubMed, Web of Knowledge, Cochrane Library and WHO International Clinical Trials Registry Platform) were searched for publications on cell signaling factors in liver regeneration and post-hepatectomy liver failure following liver resection in clinical setting. No date restriction was given. No language restriction was used. Studies were assessed using MINORS. This study was registered at PROSPERO (CRD42020165384) prior to data extraction. In total 1953 publications were evaluated for titles and abstracts after exclusion of duplicates. Full texts of 167 studies were further evaluated for inclusion. 26 articles were included in the review and 6 publications were included in the meta-analyses. High levels of serum hyaluronic acid even preoperatively are associated with PHLF but especially increased levels early after resection are predictive of PHLF with high sensitivity and specificity. Postoperative elevation of HA to levels between 100 and 500 ng/ml is increased the risk for PHLF ([OR]=246.28, 95% [CI]: 11.82 to 5131.83; p=0.0004) Inteleukin-6 levels show contradicting result in association with organ dysfunction. HGF positively correlates with liver regeneration. Overall, due to heterogeneity, scarcity, observational study design and largely retrospective analysis, the certainty of evidence, assessed with GRADE, is very low. High levels of serum hyaluronic acid show a strong association with PHLF and increased levels after resection are predictive of PHLF with high sensitivity and specificity, even on POD1. Interleukin-6 levels need to be studied further due to contradictive results in association with organ dysfunction. For HGF, no quantitative analysis could be made. Yet, most studies find positive correlation between high HGF levels and regeneration. Prospective studies investigating HGF and other growth factors, hyaluronic acid and interleukins 1 and 6 in correlation with liver regeneration measured sequentially through e.g. volumetry, and liver function parameters, preferably expanding the analysis to include dynamic liver function tests, are needed to sufficiently illustrate the connection between biomolecule levels and clinical outcomes.